Association between dietary antioxidant quality score and severity of coronavirus infection: a case–control study - Aghajani, Mobina; Wong, Alexei; Azimi, Mehdi; Harijani, Shadmehr Mirdar (Frontiers in Nutrition, 2023)
The purpose of this study was to examine the association between the dietary antioxidant quality score (DAQS) and the severity of Coronavirus disease 2019 (COVID-19). The present case–control study was carried out on 295 patients diagnosed with COVID-19 (≥18 years old), including 104 critical patients (Intensive care unit [ICU] admission) and 191 COVID-19 patients without severe complications (Non-intensive care unit [Non-ICU] patients) as cases. Dietary intake was assessed by a 147-item, semi-quantitative food frequency questionnaire (FFQ). Logistic regression was performed to calculate the odds ratio (OR) and 95% confidence interval (CI) for the considered risk factors. Our outcomes (after multivariate adjustment) suggested that higher adherence to DAQS was significantly associated with a decreased risk of COVID-19 infection severity (OR = 0.12; 95% CI: 0.04–0.29, p < 0.001). Similar results were seen when analyzed by sex [men (OR = 0.02; 95% CI: 0.002–0.15, p < 0.001) and women (OR = 0.21; 95% CI: 0.06–0.68, p = 0.012)]. A significant association between vitamin D3 intake and decreased risk of COVID-19 severity (OR = 0.91; 95% CI: 0.89–0.94, p < 0.001) was also observed. Moreover, multivariate results revealed that there were no significant associations between vitamin C (OR = 1.00; 95% CI: 0.99–1.00, p = 0.067), vitamin E (OR = 0.98; 95% CI: 0.86–1.11, p = 0.798), zinc (OR = 1.02; 95% CI: 0.86–1.20, p = 0.805), and selenium (OR = 0.99; 95% CI: 0.99–1.00, p = 0.077) intakes with the risk of COVID-19 severity. However, subgroup analyses by sex suggested a significant association between vitamin C intake and the risk of COVID-19 infection severity in women (OR = 1.00; 95% CI: 1.00–1.00, p = 0.028). Our findings showed a negative association between DAQS adherence and the risk of COVID-19 infection severity. Our results may be used to develop potential dietary therapies to decrease COVID-19 severity.